2008
DOI: 10.3325/cmj.2008.4.515
|View full text |Cite
|
Sign up to set email alerts
|

Genome Damage in Oropharyngeal Cancer Patients Treated by Radiotherapy

Abstract: Oropharyngeal cancer patients had relatively high levels of primary DNA damage in their peripheral blood lymphocytes even before therapy. The frequency of complex structural chromosome aberrations and the frequency of micronuclei increased with the progression of the radiation cycle and the doses delivered. As the frequency of chromosomal aberrations a year after radiotherapy mostly did not return to pre-therapy values, it represents an important risk factor related to the onset of second cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
14

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 38 publications
2
11
0
14
Order By: Relevance
“…On this, data in the literature are inconclusive. Whereas some authors observed that induced damage with chemotherapy or radiotherapy returned to pretreatment values in a short term (27,28), other reports show the persistence of the injury in the lymphocytes (28,29). Very few publications show long followup periods.…”
Section: Discussionmentioning
confidence: 97%
“…On this, data in the literature are inconclusive. Whereas some authors observed that induced damage with chemotherapy or radiotherapy returned to pretreatment values in a short term (27,28), other reports show the persistence of the injury in the lymphocytes (28,29). Very few publications show long followup periods.…”
Section: Discussionmentioning
confidence: 97%
“…It is suggested that genetic instability, which takes the form of delayed reproductive death (DRD), can participate in late side effects in patients treated with radiotherapy, because of damage, increased cell loss and longer recovery (Hendry, 2001). Increased level of chromosome aberrations and micronuclei was detected in the head and neck cancer patients undergoing radiotherapy within a year post treatment (Gamulin et al, 2008). DRD phenomenon associated with the presence of an increased percentage of stable and unstable chromosome aberrations in lymphocytes was detected in patients irradiated because of ankylosing spondylitis even several years after radiotherapy.…”
Section: The Potential Clinical Consequences Of Radiation Induced Bysmentioning
confidence: 97%
“…Peripheral human lymphocytes, which were proved to be sensitive to IR and previously established as suitable markers, demonstrate a DNA damage response following the exposure to IR . Real‐time PCR analysis showed that GRP78, ATG5, LC3, ATF4,XBP1, and GADD153 genes expression were elevated with increasing dose in the samples of radiotherapy patients, which are detailed graphically in Figure .…”
Section: Resultsmentioning
confidence: 89%